The Nutritive Value of Citrus Pulp (Lemon and Orange) Treated with Neurospora sitophila - K. Nazem (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2008)
The nutritive values of lemon and orange pulps treated with Neurospora sitophila fungus were assessed by chemical composition, in vitro digestibility, in situ (dry matter and nitrogen) degradation methods. The obtained data from the untreated and treated pulps with fungi were compared using t-test. Mean values of the chemical analysis for crude protein, ash, organic mater, NDF and ADF for untreated lemon pulp were 6.3, 6.2, 93.8, 21.3 and 17.9 for treated lemon pulp 25.1, 10.6, 89.4, 12.7 and 6.8 for untreated orange pulp 6.8, 6.5, 94.5, 26.1 and 20.3 and for treated orange pulp 23.2, 8.1, 91.9, 18.5 and 15, respectively. In all cases, a significant difference (P<0.01) between untreated pulp and treated pulp of lemon and orange was observed. Digestibility coefficient of DM, OM and DOMD of untreated lemon pulp were 79.3, 80.5 and 75.5 treated lemon pulp were 91.4, 93.5 and 83.5 untreated orange pulp were 81.5, 82.8 and 78.2% and treated orange pulp were 91.2, 94.5 and 86.9%, respectively. The digestibility coefficient for the treated pulps (lemon and orange) was significantly (P<0.01) higher than those untreated. The percentages of DM degradability of pulps in nylon bag after 48 hours of incubation with the out-flow rate of 0.05 were as follows: 66.3 for untreated lemon 75.2 for treated lemon 68.7 for untreated orange and 75.5 for treated orange. The DM degradability for the treated pulps (lemon and orange) was significantly (P<0.01) higher than those untreated. The effective degradability of protein after 48 hours of incubation in nylon bag with the out-flow rate of 0.05 was as follows: 12.1 for untreated lemon 73.7 for treated lemon 14.8 for untreated orange and 77.8 for treated orange. The effective degradability of protein for the treated pulps (lemon and orange) was significantly (P<0.01) higher than those untreated. In conclusion, treating citrus pulps with Neurospora sitophila increased the concentration of CP, digestibility coefficients and protein degradability.